The characteristic of anxiety and depression among medical students at the Faculty of Medicine, Universitas Udayana, Bali in 2016 - Tharsani Devi Srinivasagam; Bagus Komang Satriyasa (Intisari Sains Medis, 2020)
Background: Anxiety and depression are some of the most prevalent mental health problems, especially among medical students. This study aims to evaluate the severity of anxiety and depression and also the prevalence of anxiety and depression faced by the students of the Medical Faculty, Universitas Udayana, Bali, IndonesiaMethods: A retrospective cross-sectional study was conducted among 95 medical students from the Faculty of Medicine, Universitas Udayana, Bali, Indonesia, during January-December 2016. The variables assessed in this study were gender, nationality, the severity of anxiety and depression, frequency, causes, symptoms, and medication usage in this study. Data were analyzed using SPSS version 20 for Windows.Results: The characteristic of anxiety and depression among medical students was predominant in female (55.8%), Indonesian students (57.9%), mild severity (89.5%), once in two weeks of frequency (52.6%), and exam as the primary causes (91.6%). Besides, most symptoms of anxiety and depression were headache (100.0%) following by paracetamol usage (94.7%) as medication.Conclusion: Several characteristics of anxiety and depression found among medical students were primarily related to the female Gender, Indonesian students, exam as the primary causes, headache symptoms, and paracetamol as the main medication uses to relieve the symptoms.